Effect of temperature and dietary pesticide exposure on neuroendocrine and olfactory responses in juvenile Chinook salmon (Oncorhynchus tshawytscha). (1st February 2023) - Magnuson, Jason T.; Fuller, Neil; McGruer, Victoria; Huff Hartz, Kara E.; Acuña, Shawn; Whitledge, Gregory W.; Lydy, Michael J.; Schlenk, Daniel
Abstract: Projected water temperature increases based on predicted climate change scenarios and concomitant pesticide exposure raises concern about the responses of aquatic organisms. To better understand the effect of pesticide mixtures and influence of water temperature to fish, juvenile Chinook salmon ( Oncorhynchus tshawytscha ) were dietarily exposed to a mixture of legacy and current use pesticides ( p, p '-DDE, bifenthrin, chlorpyrifos, esfenvalerate, and fipronil) at concentrations detected from field-collected prey items in the Sacramento-San Joaquin Delta, California (Delta) and exposed under current and predicted future water temperature scenarios, 11, 14, or 17 °C, for 14 days. The expression of a subset of genes (deiodinase 2- dio2, gonadotropin releasing hormone 2- gnrh2, and catechol-o-methyltransferase- comt ) involved in neuroendocrine, dopaminergic, and olfactory function previously shown to be altered by individual pesticide exposures germane to this study were determined and olfactory function assessed using a Y-maze behavioral assay. When total body burdens of pesticides were measured, a significant decrease in dio2 expression was observed in Chinook salmon exposed at 14 °C compared to fish kept at 11 °C. Increases in gnrh2 expression were also observed in fish exposed to 14 °C. Similarly, increases in comt expression was noted at 14 and 17 °C. Additionally, altered expression of all transcripts was observed, showing interactions between temperature and individual pesticide concentrations. Chinook salmon spent significantly more time actively avoiding the odorant arm at baseline conditions of 11 °C in the Y-maze. At higher temperatures, Chinook spent significantly more time not making a choice between the odorant or clean arm following exposure to the low pesticide mixture, relative to 11 °C. These results suggest that dietary exposure to pesticide mixtures can potentially induce neuroendocrine effects and behavior. Impaired olfactory responses exhibited by Chinook salmon could have implications for predator avoidance in the wild under increased temperature scenarios and impact populations in the future. Graphical abstract: Image 1 Highlights: Pesticide mixtures and temperature induce neurobehavioral effects in Chinook salmon. Olfactory function impaired in Chinook salmon following dietary pesticide exposures. Dysregulation in expression of neuroendocrine, dopaminergic, and olfactory genes.